Pasturollesis: Complication of Metastatic Supporative pneumonia Severe Stress in Asian Elephant (Elephas maximus) - Shrivastav, AB; Rokde, Amol; Agarwal, Sandep; Shrivastav, Gaurav (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
The Asian elephant (Elephas maximus) is amega herbivores and represents one of the most critically endangered species of large mammals in the world. Few infectious diseases are responsible to decrease their number both wild and in semi-captive condition. Diseases that are shared between species also represent a potential burden to the whole ecosystem, affecting biodiversity, changing behavior or composition of animal populations, and even relegating species to the fringe of extinction (Daszak et al., 2000). Pasturollesis is an acute and often fatal disease primarily occurring in water buffaloes and cattle, but occasionally other domesticated and wild mammals and caused by particular serotypes of gram-negative bacterium Pasteurella multocida and manifested by an acute and highly fatal septicaemia.